SISTEM PEMIDANAAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Salman Paris Harahap; Madiasa Ablisar; Marlina Marlina; Suhaidi Suhaidi (Universitas Sumatera Utara, 2018)
ABSTRACT Children as criminals must be treated humanely to the best interests of the child to realize growth and provide physical, mental and social. The protection of children is also reflected in the provisions of Article 28 and paragraph (2) of the 1945 Constitution the basic rights of children, that